2008
DOI: 10.1614/wt-07-102.1
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges of Specialty Crop Weed Control, Future Directions

Abstract: The process of labeling new herbicides for specialty crops has always been difficult. Progress in solving specialty crop weed control problems will likely be more challenging in the future. Major crops like corn, cotton, rice, soybean, and wheat are planted on millions of hectares, and most of these crops are treated with herbicides. In contrast, specialty crops (i.e., minor crops, e.g., container ornamentals or lettuce) are planted on 122,000 ha or less; thus, the potential value of herbicide sales is limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 39 publications
0
67
0
Order By: Relevance
“…Minor crops, such as hemp, may be particularly affected by weeds, due to a lack of registered herbicides. Biotic stressors, such as weeds, are among the major factors that cause yield instability and even total crop failure for minor crops (Peltonen‐Sainio et al ., ), and Fennimore and Doohan () argued that research is particularly needed for minor crops in the United States, because of limited options for weed management and the small fraction of funding made available for weed research. Similarly, Santín‐Montanyá et al .…”
Section: Discussionmentioning
confidence: 99%
“…Minor crops, such as hemp, may be particularly affected by weeds, due to a lack of registered herbicides. Biotic stressors, such as weeds, are among the major factors that cause yield instability and even total crop failure for minor crops (Peltonen‐Sainio et al ., ), and Fennimore and Doohan () argued that research is particularly needed for minor crops in the United States, because of limited options for weed management and the small fraction of funding made available for weed research. Similarly, Santín‐Montanyá et al .…”
Section: Discussionmentioning
confidence: 99%
“…Hofmann et al (2006) found that $21 million compensation was paid for ladder-related injuries in the Washington State tree fruit industry between 1996 and 2001, which accounted for almost half of all compensable claims in that sector for the six-year period. Projecting into the future, the labor issue is expected to become more critical in terms of both increasing costs and uncertain availability (Fennimore and Doohan, 2008). Thus, automated or robotic harvesting system is essential to meet the increasing labor demand, to lower human risk of injuries in orchards, and to decrease the harvesting cost by saving time, money, and energy, which is profitable to both producers and consumers.…”
Section: Introductionmentioning
confidence: 99%
“…In California, there is no POST herbicide for fresh spinach, and cycloate PRE is the primary herbicide, used on about 50% of the acreage (CADPR 2013;Fennimore and Doohan 2008;USDA 2013). Cycloate applications often result in partial control of typical Salinas Valley broadleaf weeds such as burning nettle (Urtica urens L.), common purslane (Portulaca oleracea L.), and common chickweed [Stellaria media (L.) Vill.…”
mentioning
confidence: 99%